2015
DOI: 10.1186/s12957-015-0719-y
|View full text |Cite
|
Sign up to set email alerts
|

Is revisional surgery mandatory when an unexpected sarcoma diagnosis is made following primary surgery?

Abstract: BackgroundSoft tissue sarcomas (STS) are often diagnosed unexpectedly after surgery, and many excisions are incomplete. As histopathological assessments are challenging, patients later referred to comprehensive cancer centers (CCC) often come with an unclear status. This can make treatment planning problematic. We investigated the reliability of primary histopathological assessments, whether revisional surgery improved resection status, and the prognostic value of residual tumor at re-excision.MethodsWe analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 40 publications
1
43
1
Order By: Relevance
“…– 5 In our cohort, 38.6% of patients treated at one of the three centres had undergone UE outwards. The rates that we found are comparable to the 37% reported by Lewis et al and 34.8% observed by Koulaxouzidis et al6,11 …”
Section: Discussionsupporting
confidence: 92%
“…– 5 In our cohort, 38.6% of patients treated at one of the three centres had undergone UE outwards. The rates that we found are comparable to the 37% reported by Lewis et al and 34.8% observed by Koulaxouzidis et al6,11 …”
Section: Discussionsupporting
confidence: 92%
“…Residual tumor at re-excision correlates with a risk of earlier and more likely local recurrence. 6 Although not a statistically significant difference, 3 of the 7 (43%) lesions in our results excised elsewhere, or when not initially treated as sarcoma, developed metastases, compared with 2 of 9 (22%) excised after formal workup via sarcoma MDT.…”
Section: Discussioncontrasting
confidence: 52%
“…2 When an "unplanned" excision of a sarcoma is performed outside of an STS MDT, initial histopathologic assessment is considered unreliable and should not be used to plan future treatment. 6 It should always be discussed at an MDT and followed by a re-excision of the affected area if appropriate, though this may be dependent on anatomical constraints such as adjacent neurovascular structures, the additional morbidity it may cause, and potential efficacy of adjuvant therapy. Residual tumor at re-excision correlates with a risk of earlier and more likely local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rarity of STS compared to the prevalence of benign soft tissue masses, up to 50% of patients with STS will undergo a nononcologic, unplanned excision (UE) for a mass initially presumed to be benign . Patients who undergo unplanned, nononcologic resections are commonly referred to tertiary referral centers, and due to the high probability of residual tumor left in the surgical bed after UE, the current standard of care recommends re‐excision with or without radiation of the tumor bed in an effort to achieve appropriate oncologic margins and local control …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Patients who undergo unplanned, nononcologic resections are commonly referred to tertiary referral centers, and due to the high probability of residual tumor left in the surgical bed after UE, the current standard of care recommends re-excision with or without radiation of the tumor bed in an effort to achieve appropriate oncologic margins and local control. 6,[8][9][10][11][12][13][14][15][16] Historically, patients who undergo UE have been described as having worse oncologic outcomes compared with patients who undergo planned oncologic excision (PE) primarily, explained by fragmented excisions and disruptions of the tumor capsule associated with UE. 15,17 Subsequent reports have shown that patients who undergo UE have similar, or even improved, recurrence-free, metastasis-free, and disease-specific survivals compared with patients with planned excisions.…”
Section: Introductionmentioning
confidence: 99%